Air pollution and urinary n-acetyl-B-glucosaminidase levels in residents living near a cement plant. Issue 1 (December 2016) - Jung, Min; Kim, Jae; Lee, Hyun; Lee, Chul; Song, Han
Abstract Background To identify adverse renal effects due to air pollution derived from a cement plant in Korea. Urinary n-acetyl-B-glucosaminidase (U-NAG) levels in residents living near a cement plant were compared to those in a group who lived farther away from the plant. Methods From June to August 2013 and from August to November 2014, laboratory tests for U-NAG and heavy metal were conducted on 547 study participants. Based on the level of air pollution exposure, subjects were divided into the "less exposed group, " (LEG) which consisted of 66 persons who lived more than 5 km away from the cement plant, the "more exposed group from the rural area" (MEG-R), which consisted of 272 persons, and the "more exposed group from downtown area" (MEG-D), which consisted of 209 persons who lived within a 1 km radius of the cement plant. U-NAG levels >5.67 U/L were defined as "higher U-NAG" levels. We compared the prevalence of higher U-NAG levels and estimated the adjusted odds ratio (OR) by air pollution exposure using a chi-square test and multiple logistic regression analysis. Further, we estimated the interaction between air pollution exposure and heavy metal exposure in renal toxicity. Results The OR of higher U-NAG levels by MEG-D and MEG-R compared to LEG was 2.13 (95 % CI 0.86–4.96) and 4.79 (95 CI 1.65–10.01), respectively. Urinary cadmium (U-Cd), urinary mercury (U-Hg), age, occupation, hypertension, and diabetes had a significant association with higher U-NAG levels. However, blood lead (B-Pb), sex, and smoking were not associated with higher U-NAG. Especially, concurrent exposure to heavy metals (U-Hg or/and U-Cd) and air pollution had an additive adverse effect. In the group with both 4th quartile heavy metal exposure (U-Cd or/and U-Hg) and air pollution exposure, the OR in MEG-R and MEG-D was 6.49 (95 % 1.42–29.65) and 8.12 (95 % CI 1.74–37.92), respectively, after adjustment for age, occupation, hypertension, diabetes. Conclusions U-NAG levels seem to be affected by air pollution exposure as well as age, hypertension, diabetes, and even low levels of cadmium and low levels of mercury. Moreover, concurrent exposure to heavy metals and air pollution can have additive cytotoxic renal effects.